Measurement Invariance of the Five Factor Model of Personality: Facet-Level Analyses Among Euro and Asian Americans. (July 2020) - Lui, P. Priscilla; Samuel, Douglas B.; Rollock, David; Leong, Frederick T. L.; Chang, Edward C.
Relative to broad Big Five domains, personality facets provide incremental value in predicting life outcomes. Valid between-group comparisons of means and correlates of facet scores are contingent upon measurement invariance of personality measures. Research on culture and Big Five personality has been largely limited to cross-national comparisons of domains, without assessing measurement invariance across ethnoracial groups within the same country. Using the NEO Inventories, we tested facet-level measurement invariance between Euro ( N = 418, 63.2% women, Mage = 18.43) and Asian Americans ( N = 429, 56.6% women, Mage = 18.00). Multigroup exploratory factor analysis within a confirmatory factor analysis framework showed partial strong invariance. Assertiveness and activity did not load onto extraversion as strongly for Asian Americans. Self-consciousness showed a stronger cross-loading onto extraversion among Asian Americans than Euro Americans. Achievement striving, competence, warmth, tender-mindedness, and excitement seeking showed noninvariant intercepts across groups. Collectivistic values emphasizing interpersonal harmony and modesty should be considered when examining narrow and broad traits among Asian Americans.